Адаптивный алгоритм сжатия изображений для создания пиксель-арта - Телюх, О. И. (My University, 2018)
Introduction of a content-adaptive image downscaling method for pixelart usage. The key idea is to optimize the shape and locations of the downsampling kernels to better align with local image features. Contentadaptive kernels are formed as a bilateral combination of two Gaussian kernels defined over space and color, respectively. This yields a continuum ranging from smoothing to edge/detail preserving kernels driven by image content. This is technically realized as an iterative maximum-likelihood optimization using a constrained variation of the Expectation-Maximization algorithm. The main task of this algorithm is creating pixel art images from raster or vector graphics inputs, due to its ability to keep linear features sharp and connected.
Keywords: сжатие изображение; пиксель-арт